Validation of a cutoff for the Depression Scale of the Center for Epidemiologic Studies, Brief Version (CESD-7). - Aarón Salinas-Rodríguez; Betty Manrique-Espinoza; Isaac Acosta-Castillo; Martha Ma. Téllez-Rojo; Aurora Franco-Núñez; Luis Miguel Gutiérrez-Robledo; Ana Luisa Sosa-Ortiz (Instituto Nacional de Salud Pública, 2013)
Objective. To evaluate the Depression Scale of the Center for Epidemiologic Studies, Brief Version (CESD-7) psychometric properties in Mexican adult population, and validate a cutoff for classifying subjects according to the presence / absence of clinically significant depressive symptoms (CSDS). Materials and methods. Screening cross-sectional study with a subsample of 301 adult residents of the Morelos state in Mexico, originally interviewed for the National Survey of Health and Nutrition 2012. Sensitivity and specificity of the selected cutoff were estimated using as reference the diagnostic criteria of ICD-10 and DSM-IV. Results. The cutoff point estimated was CESD-7=9. Using the ICD-10 the sensitivity and specificity were 90.2 and 86%, and ROC was 88%. Using DSM-IV, the values were 80.4, 89.6, and 85%, respectively. Conclusions. The short version of the CESD-7 has good psychometric properties and can be used as a screening test to identify probable cases of subjects with clinically significant depressive symptoms.